2017
DOI: 10.1016/j.rboe.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Posterior three-column osteotomies for the treatment of rigid thoracic kyphosis – a case series

Abstract: ObjectiveTo evaluate the results and complications of a series of patients who underwent three-column osteotomy using the posterior approach for correction of complex cases of rigid dorsal kyphotic deformity.MethodsReview of clinical records and images of 15 consecutive cases of pedicle subtraction osteotomies, bone-disk-bone osteotomies, or vertebral column resection, recording the etiology, type and level of osteotomy, extension of fixation, complications, and pre- and post-surgical measurements of the sagit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…According to the relationship between hemivertebrae and upper and lower vertebrae, CS can be divided into three types: fully segmented hemivertebra, partially segmented hemivertebra, and non-segmented hemivertebra (1,2). CS deformity in children is complex and even serious at birth, and develops continuously with growth; therefore, most scholars advocate early surgical treatment to block the progress of spinal deformity (3,4). Surgical treatment methods include in situ fusion, convex epiphyseal block, hemivertebra resection, and spinal fusion.…”
Section: Introductionmentioning
confidence: 99%
“…According to the relationship between hemivertebrae and upper and lower vertebrae, CS can be divided into three types: fully segmented hemivertebra, partially segmented hemivertebra, and non-segmented hemivertebra (1,2). CS deformity in children is complex and even serious at birth, and develops continuously with growth; therefore, most scholars advocate early surgical treatment to block the progress of spinal deformity (3,4). Surgical treatment methods include in situ fusion, convex epiphyseal block, hemivertebra resection, and spinal fusion.…”
Section: Introductionmentioning
confidence: 99%
“…17 Although classical articles show local mobilizations of 30 to 40º with pedicle subtraction, in multicenter studies the average for the same procedure is only 22º. Previous observations 19 have shown that in osteotomies performed in patients with dorsal spine pathologies and compensated overall balance, corrections tend to be maintained, such that in this series we opted to use a worse scenario and include only imbalanced patients. Although an SVA above 5cm is defined as imbalance, some authors treat an SVA up to 8cm as acceptable.…”
Section: Discussionmentioning
confidence: 98%